The Concept of ‘Freedom’ in Contemporary Russian Poetry - Graf, Alexander (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article surveys the concepts of ‘freedom’ (svoboda) in contemporary Russian poetry and points out that there is no single understanding of it but a whole complex of approaches. While the concept of svoboda seems to have been absorbed by the bigger and therefore less concrete one, volya, a certain evolution of the former notion can be observed as well. At the beginning of the 20th century ‘freedom’ was associated with a heroic attitude, during the Thaw it became a term for a collective domestic separation, after perestroika and glasnost the poets started to look for freedom as individuals, having nothing or very little in common with the society. Over the last years a new kind of inner emigration has been evolving, combined with a tendency towards ostentatious indifference to ‘traditional’ values.